Japanese Information in science, technology and commerce : (IOS Press, 1990)
Proceedings of the 2nd international conference held by Gesellschaft für Mathematik und Datenverarbeitung in co-operation with Japanisch Deutsches Zentrum Berlin, Staatsbibliothek Preussischer Kulturbesitz on 23-25 October 1989, in Berlin (West)